The challenge of the surgical treatment of paediatric distal radius/ forearm fracture: K wire vs plate fixation - outcomes assessment - Di Giacinto, Salvatore; Pica, Giuseppe; Stasi, Alessandro; Scialpi, Lorenzo; Tomarchio, Alessandro; Galeotti, Alberto; Podvorica, Vlora; dell’Unto, Annamaria; Meccariello, Luigi (Medicinski glasnik, 2021)
Aim Distal radius/forearm fractures in adolescent patients remain challenging injuries to treat. Distal radius/forearm bony anatomy is not completely restored with intramedullary K wire fixation. The aim of this study was to compare radiographic and functional outcomes obtained using intramedullary K wire fixation and open reduction and internal fixation in the treatment of distal radius/forearm fracture. Methods A total of 43 patients who presented with distal radius/forearm fractures were enrolled and divided into two groups: 23 patients treated with K-wire (IMNK) and 20 patients treated with plate and screws (ORIF). The evaluation criteria were: fracture healing time, objective quality of life measured by the Mayo wrist score (MWS) and quick disabilities of the arm, shoulder and hand score (QuickDash), length time of surgery, complications, sport or play return, forearm visual analogic pain (FVAS), bone healing by radius union scoring system (RUSS). Results In both groups the results obtained were comparable in terms of functional, pain and return to play/sport after the third month after surgery. Bone healing was faster in IMNK than ORIF but without significance (p>0.05). There was less complication in ORIF than IMNK (p<0.05). Conclusion The treatment of adolescent distal radius or forearm fractures remains challenging. One challenge facing the physician is the choice of surgical technique and fixation method, which will be influenced by individual experience and preference. The question of distal radius or forearm fractures in adolescents would be best answered with a prospective randomized study.